Analisis Molekuler Bakteri Endofit SH 14 dari Mangrove Scyphiphora hydrophyllacea Pantai Rendani - Yamco, Fallen; Massora, Maria; A. Mogea, Rina (Program Pascasarjana Universitas Papua, 2024)
ABSTRACT: The mangrove endophytic bacterial isolate Scyphiphora hydrophyllacea has antimicrobial capabilities and also has other bioactive compounds to be developed in the field of biotechnology. The aim of this study was to identify the endophytic bacterial isolate SH 14 obtained from the S. hydrophyllacea mangrove based on 16S rDNA sequence analysis. Molecular-based identification of bacteria, namely DNA amplified by Polymerase Chain Reaction (PCR) using primers 27F and 1492R and has a gene amplification of 1481 bp. Sequence data analyzed using the BLAST program showed that isolate SH 14 had a homology level of 99.43% with Brevibacillus brevis. This similarity value is a reference in determining bacterial identification, where bacteria are categorized as the same species if they have a similarity of 99%.